(untitled) (Studia Prawnicze / The Legal Studies, 2008)
Przedmiotem niniejszego opracowania są zagadnienia związane z problematyką stosowania w postępowaniu w sprawie kontroli konstytucyjności przesłanki zbędności orzekania. Biorąc pod uwagę, że obecnie stanowi ona jedną z najczęstszych przyczyn umarzania postępowania warto dokonać szczegółowej analizy obejmującej regulację prawną oraz dotychczasowe orzecznictwo Trybunału Konstytucyjnego w celu określenia znaczenia i treści omawianej ujemnej przesłanki procesowej. Przed dokonaniem wskazanej analizy przesłanki zbędności omówiono rodzaje, a talcże znaczenie i charakter przesłanek postępowania w sprawie kontroli konstytucyjności. W dalszej kolejności przedstawiono analizę orzecznictwa Trybunału Konstytucyjnego obejmująca okres od wejścia w życie ustawy z 1 sierpnia 1997 r. o Trybunale Konstytucyjnym1 (dalej: ustawa o TK) do dnia 31 sierpnia 2008 r. w zaluesie sytuacji, w których uznawano zbędność orzekania. ’W końcowej części, w oparciu o przeprowadzoną analizę określono charakter oraz wskazano znaczenie i treść omawianej przesłanki postępowania. Polish legislator has determined a number of conditions of admissibility of initiating of constitutional review proceeding. In proceeding before the Con stitutional Tribunal there are several prerequisites for court proceeding and one substantial prerequisite. Non-fulfilment of any of the positive prerequisites or appearance of even of one of negative prerequisite causes inadmissibility of proceeding. In every case it is necessary to point out a specific prerequisite of proceeding causing its inad missibility Superfluity of proceeding constitutes one of negative prerequisite for court proceeding which causes discontinuance. Research of jurisprudence of the Con stitutional Tribunal shows several different reasons causing superfluity of ad jugment. Mainspring of superfluity is re-challenging of a provision which has already been reviewed by prior decision. If the Constitutional Tribunal find chal lenged regulation unconstitutional, re-adjugment of this regulation is super fluous because the main goal of constitutional review (i.e. removal of inconsis tency of legal system) has already been achieved. In turn, if the Tribunal find challenged regulation constitutional and the petitioner does not indicate new argumentation, re-adjugment of this regulation is pointless due to lack of new ground for review. To sum up, if the proceeding does not serve restitution of constitutionality it cannot be conducted due to superfluity. That situation takes place when the main goal of constitutional review has already been achieved.